PENGARUH PEMANFAATAN TEKNOLOGI INFORMASI PENGAWASAN KEUANGAN DAERAH SUMBER DAYA MANUSIA DAN PENGENDALIAN INTERN AKUNTANSI TERHADAP KETERANDALAN PELAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Pada SKPD Kabupaten Indragiri Hulu) - Putri Larassati; Andreas '; Supriono ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this research to examined the influence of information technology utilization, control of financial statements, human resources, and internal control accounting on the local government financial reporting reliability at SKPD of Indragiri Hulu. The population in this study were employed who worked in the SKPD of Indragiri Hulu. This research used 75 sample of quetionnaires response from employed who workes in the SKPD of Indragiri Hulu by using purposive sampling method. Analysis model used in this study is the multiple linear regression analysis with SPSS Version 20.00. The result of this study is showed that information technology utilization, local financial monitoring, human resources, and internal control accounting have significant influence on the local government financial reporting reliability. Simultaneous regression test (F-test) showed that all dependent variable have significant influence to the dependent variable. The coefficient determination (R2) effect by all independent variable are 85,9% while the remaining 14,1% influence by other variables were not examined in this study.Keyword : Information Technology Utilization, Control Of Financial Statements, Human Resources, Internal Accounting Control, Local Government Financial Reporting